An analytical modeling and estimating losses of power semiconductors in a three-phase dual active bridge converter for MVDC grids - Lee, Youngsil; Vakil, Gaurang; Watson, Alan James; Wheeler, Patrick (2016)
Due to the increasing installation of renewable and decentralized power sources, Medium-voltage dc (MVDC) grids has been considered for an alternative application to medium-voltage ac (MVAC) application. Three-phase dual active bridge DC-DC (3DAB) converter is proposed as an attractive topology for MVDC grids due to its high power capability, smaller filtering parts, and galvanic isolation. In this paper, a first harmonic approximation (FHA) modeling of 3DAB converter is derived. Using the FHA modeling, a symmetrical modeling of switching devices is introduced and a 4MVA system for 40kV MVDC system has been validated in terms of conduction and switching losses. Experimental implementation of a 10kVA prototype and the results are presented.